2022
DOI: 10.36660/abc.20210492
|View full text |Cite
|
Sign up to set email alerts
|

Estimuladores de Guanilato Ciclase Solúvel (Riociguate) na Hipertensão Pulmonar: Dados da Prática Clínica Real em 3 Anos de Acompanhamento

Abstract: Resumo Fundamento A hipertensão pulmonar (HP) é uma doença rara e complexa com prognóstico ruim, que exige tratamento pela vida toda. Objetivo Descrever dados de 3 anos de acompanhamento da vida real sobre o tratamento com estimuladores de guanilato ciclase solúvel (Riociguate) de pacientes com HP, medindo parâmetros atuais de avaliação de risco. Métodos Coletamos dados clínicos e epidemiológicos retrospectivamente de pacientes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Previously, Ghofrani et al 7 demonstrated that riociguat, through the direct activation of GCs, promoted an increase in cyclic GMP and consequently pulmonary vasodilation, and its administration 3 times daily in patients with PAH improved serum N terminal pro B type natriuretic peptide (NT-proBNP) concentrations, time to clinical worsening, and WHO functional class. 7 Reduction of NT-proBNP levels was not observed by Spilimbergo et al, 6 possibly explained by the small number of patients included in the study. Similarly, in 2015, the CHEST-2 study described that long-term administration of riociguat in patients with CTEPH improved exercise and functional capacity.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previously, Ghofrani et al 7 demonstrated that riociguat, through the direct activation of GCs, promoted an increase in cyclic GMP and consequently pulmonary vasodilation, and its administration 3 times daily in patients with PAH improved serum N terminal pro B type natriuretic peptide (NT-proBNP) concentrations, time to clinical worsening, and WHO functional class. 7 Reduction of NT-proBNP levels was not observed by Spilimbergo et al, 6 possibly explained by the small number of patients included in the study. Similarly, in 2015, the CHEST-2 study described that long-term administration of riociguat in patients with CTEPH improved exercise and functional capacity.…”
mentioning
confidence: 80%
“…Thus, it is essential to search for pulmonary vasodilators that interfere with this relevant molecular pathways. 5 In issue of the Arquivos Brasileiros de Cardiologia, Spilimbergo et al 6 report a follow-up study in which patients with PH were treated with an GCs stimulant, riociguat, which is approved for treating PAH because it augments the nitric oxide (NO)-cyclic GMP pathway. The authors describe live cases outcome spanning 3 years, focusing on PAH (type 1) and chronic thromboembolic PH (CTEPH, type 4).…”
mentioning
confidence: 99%
“…12 This biomolecular signaling is mainly explained by the opening of mitochondrial K ATP channels in cardiac cells. 12 In their groundbreaking paper of 2022, Spilimbergo et al 13 were the first researchers to retrospectively investigate the effects of riociguat in patients with PAH and CTEPH through a 3-year follow-up real-life study. 13 These scientists measured current risk assessment parameters and found interesting data which may help to prove the beneficial effects of riociguat in PAH and CTEPH subjects.…”
mentioning
confidence: 99%
“…12 In their groundbreaking paper of 2022, Spilimbergo et al 13 were the first researchers to retrospectively investigate the effects of riociguat in patients with PAH and CTEPH through a 3-year follow-up real-life study. 13 These scientists measured current risk assessment parameters and found interesting data which may help to prove the beneficial effects of riociguat in PAH and CTEPH subjects. 13 Firstly, they have shown that riociguat significantly increased the 6-minute walking distance (6MWD) after at least 3 years of therapy, compared with the baseline data, in both patients with PAH and CTEPH.…”
mentioning
confidence: 99%
See 1 more Smart Citation